The nation’s unfinished dead: haunting, archival silence, and the politics of memory in post-authoritarian Indonesian novels - Awla Akbar Ilma (Indonesian Journal of Politics and Literary Studies, 2026)
Background: Post-authoritarian Indonesian fiction emerges from a national memory field marked by unresolved political death, forced disappearance, inherited stigma, and incomplete public reckoning with authoritarian violence. Objective: This study aims to examine how post-authoritarian Indonesian novels narrate haunting, archival silence, and necropolitical memory as literary responses to unfinished death and contested national belonging. Method: Using qualitative literary analysis, this study combines close reading, coded narrative-unit analysis, and memory-oriented discourse analysis across selected novels and contextual scholarly sources. Results: Findings show that haunting appears most strongly as temporal residue, where past violence continues through fugitivity, exile, delayed searching, family memory, and inherited fear rather than through literal ghostly presence alone. Findings also indicate that archival silence functions as a counter-archival force, enabling novels to transform missing documents, suppressed testimony, family fragments, and absent bodies into alternative modes of remembrance. Implication: Findings further reveal that necropolitical memory positions dead, disappeared, exiled, and stigmatized subjects as unstable members of national history, exposing unequal access to mourning, recognition, and symbolic belonging. Novelty: This study offers novelty by conceptualizing unfinished death as an integrated analytical category linking hauntology, archival silence, and necropolitical memory in post-authoritarian Indonesian literary studies.